The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1993
DOI: 10.1002/ccd.1810300310
|View full text |Cite
|
Sign up to set email alerts
|

Emergency coronary stenting for acute occlusive dissection of the left main coronary artery

Abstract: Catheter-induced left main coronary artery dissection is a rare but serious complication of diagnostic cardiac angiography. We report the case of a patient with mitral regurgitation and accidental dissection of the left main coronary artery successfully managed with intracoronary stent that allowed emergent surgical revascularization and mitral replacement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…However, recently some reports have begun to appear in the literature concerning stenting of unprotected LMCA disease in patients with very high surgical risks or severe comorbid conditions. [19][20][21] For this reason, this technique has been shown to be highly effective in preventing elastic recoil and abrupt vessel closure, thereby improving the acute result of PTCA. In our study, stent implan-tation was performed in 5 patients and successful left coronary artery dilatation was achieved in all patients.…”
Section: -13)mentioning
confidence: 99%
“…However, recently some reports have begun to appear in the literature concerning stenting of unprotected LMCA disease in patients with very high surgical risks or severe comorbid conditions. [19][20][21] For this reason, this technique has been shown to be highly effective in preventing elastic recoil and abrupt vessel closure, thereby improving the acute result of PTCA. In our study, stent implan-tation was performed in 5 patients and successful left coronary artery dilatation was achieved in all patients.…”
Section: -13)mentioning
confidence: 99%
“…This is exemplified by the results of one of the largest series of LMCA angioplasty, in which O'Keefe et al [6] reported a 9.1% procedural mortality and a 3-year survival rate of only 36% in unprotected left main stenosis, against 2.4% and 90%, respectively, in protected ones. With the availability of the Palmaz-Schatz coronary stent in the early 1990s, cardiologists began to use this device for treatment of unprotected LMCA disease, usually as a bailout in acute left main dissection [11,12] or as an alternative to CABG in patients with high surgical risk or severe comorbid conditions [13]. Despite the reported successes, there remain three main concerns in stenting of unprotected LMCA stenosis: acute safety, technical difficulties, and long-term clinical results of the procedure.…”
Section: Discussionmentioning
confidence: 98%
“…It has also been shown in randomized trials to reduce restenosis compared with balloon angioplasty [9,10]. Anecdotal reports began to appear in the literature about stenting of unprotected LMCA disease, either as a bailout procedure or as a compassionate alternative in patients with very high surgical risks or severe comorbid conditions [11][12][13]. The LMCA, however, has a unique anatomy.…”
Section: Introductionmentioning
confidence: 97%
“…[2][3][4][5]11 In the present study, all patients with LMCA dissection were successfully treated with stent deployment. Treatment options for this complication include intracoronary stenting and emergency CABG.…”
Section: Discussionmentioning
confidence: 99%
“…In this circumstance, stent implantation could be the fastest technique in achieving vessel patency and stabilizing hemodynamic status. [2][3][4][5] We therefore assumed that prompt stent implantation for LMCA dissection is safe and associated with favorable clinical outcome. To test this hypothesis, we retrospectively evaluated the acute and long-term results of bail-out stenting for LMCA dissection occurring during a catheter-based procedure.…”
Section: Introductionmentioning
confidence: 99%